Wingless-type family member 3A triggers neuronal polarization via cross-activation of the insulin-like growth factor-1 receptor pathway - Bernis, Maria E.; Oksdath, Mariana; Dupraz, Sebastian; Nieto Guil, Alvaro F.; Fernandez, Marisa M.; Malchiodi, Emilio L.; Rosso, Silvana B.; Quiroga, Santiago (Frontiers in Cellular Neuroscience, 2013)
Initial axonal elongation is essential for neuronal polarization and requires polarized activation of IGF-1 receptors (IGF-1r) and the phosphatidylinositol 3 kinase (PI3k) pathway. Wingless-type family growth factors (Wnts) have also been implied in the regulation of axonal development. It is not known, however, if Wnts have any participation in the regulation of initial axonal outgrowth and the establishment of neuronal polarity. We used cultured hippocampal neurons and growth cone particles (GCPs) isolated from fetal rat brain to show that stimulation with the wingless family factor 3A (Wnt3a) was sufficient to promote neuronal polarization in the absence of IGF-1 or high insulin. We also show that Wnt3a triggered a strong activation of IGF-1r, PI3k, and Akt in developmental Stage 2 neurons and that the presence of activatable IGF-1r and PI3k activation were necessary for Wnt3a polarizing effects. Surface plasmon resonance (SPR) experiments show that Wnt3a did not bind specifically to the IGF-1r. Using crosslinking and immuno-precipitation experiments, we show that stimulation with Wnt3a triggered the formation of a complex including IGF-1r-Wnt3a-Frizzled-7. We conclude that Wnt3a triggers polarization of neurons via cross-activation of the IGF-1r/PI3k pathway upon binding to Fz7.